The Analysis of American and British English's Vocabularies - Maryam Lughu (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
The analysis of American and British English's Vocabularies. The purpose of thisresearch was to find out and analyze the vocabularies in American English andBritish English. The research was held by using the qualitative descriptive analysismethod and library research where data made in form of words, sentences,quotations or definitions by using the sources of data from books, articles alsojournals which the data related to the analysis. It was found from the research thatalthough there were similarities between American and British English but it wasalso found the differences, that is : (1). Past and Past Participle Forms of Verb, (2).Past Simple Vs Present Perfect, (3). Subject-verb Agreement, (4). Prepositions, (5).Vocabulary Differences, (6). Writing Dates, (7). Articles, (8). Auxiliary verbs, (9).Tag questions and (10). Spelling, (11). Punctuation, (12). StressKeywords : Vocabularies, American English, British English